Identification of virulence-related amino acid mutations of avian encephalomyelitis virus associated with vaccination methods - Xu, Zheng; Fan, Pengcheng; Zhang, Chengcheng; Guo, Mengjiao; Bo, Zongyi; Wu, Yantao; Zhang, Xiaorong (Frontiers in Veterinary Science, 2025)
Avian encephalomyelitis virus (AEV), a picornavirus, primarily infects the central nervous system of 1 to 2-week-old young chickens but not pullets. When wild-type AEV undergoes serial passaging in chicken embryos, it becomes to be embryo-adapted and can cause avian encephalomyelitis in chickens of all ages following intracutaneous infection through parenteral routes. This study was conducted to explore whether an outbreak of AEV in 95-day-old chickens was linked to inadvertent embryo adaptation of the AEV vaccine and its association with vaccination method. In this study, an AEV strain AEV/JS202201 was isolated from the flocks of chickens that had been shortly after vaccinated with the AEV vaccine combined with the avian pox vaccine by the wing-web method. Whole-genome sequencing was performed on the isolated AEV/JS202201 and the immunized VACCINE X strain. The results showed that the length of AEV/JS202201 and VACCINE X strain was determined to be 7,032 bp and 7,034 bp, respectively (both excluding the poly A tail). Compared with VACCINE X strain, one mutation, T24A, were found at the VP4 in the isolated AEV/JS202201 strain. Multiple sequence alignment revealed that no other AEV strains exhibited this mutation. Animal regression experiment confirmed that AEV/JS202201 could infect layer pullets and caused typical pathological changes in brain tissue, with a higher morbidity rate (4/10) and more severe clinical symptoms in chickens immunized via the wing-web method compared to those immunized orally (2/10). In summary, this study found a potential virulence-related mutation in the VP4 protein of AEV and emphasized that the oral vaccine method is safer than the wing-web method.